Single-Step Versus 2-Step Management of Huge Pancreatic Pseudocysts. Issue 4 (May 2015) - Yuan, Haicheng; Qin, Mingfang; Liu, Rong; Hu, Sanyuan
<x xml:space="preserve">Abstract</x> Objectives Single-step endoscopic ultrasonography–guided puncture through the stomach to insert a double-pigtail stent to drain a pseudocyst usually resulted in a high infection rate. The 2-step method, which combines the single-step method with a nasocystic drain, was created to help alleviate infections. Our study compared the 2 management strategies. Methods Between January 2007 and December 2011, patients with huge pancreatic pseudocysts were randomized into either a single-step or a 2-step treatment. Complications from infections and long-term results assessed during follow-up for the 2 groups were compared. Results Forty-seven patients were enrolled—23 in the single-step group and 24 in the 2-step group. There were significant differences in the infection rates (56.52 vs 20.83, P < 0.05), the average days of hospitalization (22.96 ± 2.82 days vs 10.38 ± 1.35 days, P < 0.05), postoperative hospital stay (15.31 ± 3.82 days vs 7.21 ± 1.61 days, P < 0.05), and the disappearance time of the pseudocyst (14.10 ± 2.33 weeks vs 11.70 ± 2.21 weeks, P < 0.05) between the 2 groups; however, there was no significant difference in the pseudocyst recurrence rate. Conclusions The preferred treatment of a huge pancreatic pseudocyst is a combined endoscopic ultrasonography method using 2 double-pigtail stents and a nasocystic drain.